Identification of the Capabilities of the Kerek Sandstone Unit as a Hydrocarbon Reservoir in the Karangkepoh Area and Surrounding Areas, Boyolali, Central Java - Dwi Wahyu Hardiyanto; Adelia Saras Nugraheni (Mataram University, 2026)
Karanggede is part of the Kendeng Zone physiography, which was formed by compressional tectonics since the Middle Oligocene. This zone consists of deep marine to transitional sedimentary deposits with hydrocarbon reservoir potential. The Kerek Formation in the study area is dominated by layered carbonate sandstone and carbonate mudstone. The study site is located in Karangkepoh Village, Karanggede District, Boyolali Regency, Central Java. Geologically, this unit has undergone structural deformation that affects the physical properties of the reservoir rock. This study aims to evaluate the quantity and quality characteristics of the Kerek Formation carbonate sandstone as a hydrocarbon reservoir. The research methods include field observations and laboratory analysis of porosity and permeability parameters. The test results show very low porosity values, ranging from 1.53% to 1.78%. These porosity values indicate the rock's limited ability to store fluids. In contrast, the permeability values range from 98.53 mD to 906.74 mD. These permeability values are classified as good to very good. This condition indicates the presence of fluid flow paths that develop despite limited effective pore space. The relatively high permeability is controlled by grain size and inter-pore connectivity. The rock texture relationship plays a significant role in determining reservoir characteristics. Overall, the carbonate sandstone of the Kerek Formation in the study area acts primarily as a fluid-flow medium rather than a storage medium.